Assessing Storytelling Competencies in Indonesian Elementary Education: A Profile Study of Sixth-Grade Students - Arifin, Moch. Gusnul; Hendratno, Hendratno; Sukartiningsih, Wahyu; Istiq'faroh, Nurul; Purwoko, Budi (Journal of Innovation and Research in Primary Education, 2025)
Storytelling skills are essential components of oral communication that reflect a student’s ability to convey ideas effectively, creatively, and engagingly. This study aimed to identify the initial profile of storytelling skills among sixth-grade students (n=26) at SDN Ploso V/176 in Surabaya. The research employed a qualitative descriptive design using structured observations as the primary method of data collection. Twenty-six students participated as research subjects. The observation instrument assessed five key indicators: fluency in conveying story content, appropriate sentence intonation, facial expression and body movement, speech articulation, and clarity of voice volume. The findings revealed that, overall, the storytelling skills of the students were categorized as "fair" with an average score of 66. The highest performance was observed in the "voice volume" indicator (score: 73), while the lowest was in "facial expression and body movement" (score: 60). These findings highlight the need for targeted instructional strategies that can enhance nonverbal communication aspects such as expression and body language. Additionally, the study serves as a reference for future research to explore interventions that improve oral literacy skills in primary education. A key limitation of this study is its focus on a single school, which may affect the generalizability of the findings. The study provides valuable insights for educators and policymakers in designing more inclusive and engaging learning environments that foster oral literacy and student confidence.